Kolaborasi Pembelajaran Aqidah dan Bahasa Inggris; Peluang dan Tantangan di Era Globalisasi - Syakbi; Raiyan; Nelly Mursyidah; Farhan Raid Suhi (Pendidikan Al-Gafari, 2024)
The integration of Aqidah (Islamic creed) and English language education presents both opportunities and challenges in contemporary schooling. While globalization demands proficiency in English, it is crucial that Islamic values are preserved in the educational process. This research aims to explore the potential of combining Aqidah and English language teaching in order to create a comprehensive approach that nurtures both faith and linguistic skills in students. The study employs a qualitative research design, utilizing interviews and surveys with educators and students from Islamic schools. Data were collected through open-ended questions, and thematic analysis was applied to identify emerging trends. The findings indicate that integrating Aqidah with English language learning provides a holistic approach to education, enhancing students' understanding of both religious principles and language skills. However, challenges such as a lack of relevant teaching materials and insufficient teacher training were noted. This study concludes that a strategic approach to curriculum development, teacher training, and resource integration is essential for the successful implementation of this collaborative model. It is recommended that future research further investigates the practical applications and long-term effects of this integration on student performance and character development.